2014
DOI: 10.1007/s00247-014-3201-z
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose from multidetector CT studies in children: results from the first Italian nationwide survey

Abstract: This study reviewed practice in Italian centres performing paediatric imaging with MDCT scanners. The variability of doses among centres suggests that the use of standardised CT protocols should be encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 19 publications
1
26
1
Order By: Relevance
“…Of these, 3920 children (97 %) had US only (2352 males/1700 females, mean age 68 months, median 70 months), and 132 patients (3 %, 74 males/58 females; mean age 76 months, median 78 months) had both US and CT performed within 24 h. CT radiation dose ranged between 0.67 and 4.2 mGy. CT radiation doses in our study population are comparable to doses reported in several published national surveys [15,16].…”
Section: Resultssupporting
confidence: 85%
“…Of these, 3920 children (97 %) had US only (2352 males/1700 females, mean age 68 months, median 70 months), and 132 patients (3 %, 74 males/58 females; mean age 76 months, median 78 months) had both US and CT performed within 24 h. CT radiation dose ranged between 0.67 and 4.2 mGy. CT radiation doses in our study population are comparable to doses reported in several published national surveys [15,16].…”
Section: Resultssupporting
confidence: 85%
“…WBMR due to its high soft tissue resolution, its multiplanarity and the lack of ionising radiation exposure, should be considered the imaging modality of choice in these classes of patients, since it provides a safe assessment of the typical features of HFS, the localization of nodules, and affords to rule out or detect visceral involvement. WBMR should be preferred in paediatric patients follow up due to the possible frequent evaluation of disease activity during therapy or after surgical resection, in these cases a radiation free technique becomes mandatory [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…47 When possible, CT should be avoided in children, because they have a longer remaining life expectancy than adults and intrinsic higher vulnerability to the effects of ionising radiation, and because the chronic course of CD requires repeated lifelong examinations. [20][21][22]51 Use of CT should be limited to acute situations and not in lifetime follow-up. [20][21][22]46,47,51…”
Section: Computed Tomographymentioning
confidence: 99%
“…[20][21][22]51 Use of CT should be limited to acute situations and not in lifetime follow-up. [20][21][22]46,47,51…”
Section: Computed Tomographymentioning
confidence: 99%
See 1 more Smart Citation